Longitudinal network model of the co-development of temperament, executive functioning, and psychopathology symptoms in youth with and without ADHD. (December 2021) - Karalunas, Sarah L.; Antovich, Dylan; Goh, Patrick K.; Martel, Michelle M.; Tipsord, Jessica; Nousen, Elizabeth K.; Nigg, Joel T.
Abstract: Attention-deficit hyperactivity disorder (ADHD) is a common, chronic, and impairing disorder, yet presentations of ADHD and clinical course are highly heterogeneous. Despite substantial research efforts, both (a) the secondary co-occurrence of ADHD and complicating additional clinical problems and (b) the developmental pathways leading toward or away from recovery through adolescence remain poorly understood. Resolving these requires accounting for transactional influences of a large number of features across development. Here, we applied a longitudinal cross-lagged panel network model to a multimodal, multilevel dataset in a well-characterized sample of 488 children ( n ADHD = 296) to test Research Domain Criteria initiative-inspired hypotheses about transdiagnostic risk. Network features included Diagnostic and Statistical Manual of Mental Disorders symptoms, trait-based ratings of emotional functioning (temperament), and performance-based measures of cognition. Results confirmed that ADHD symptom domains, temperamental irritability, and working memory are independent transdiagnostic risk factors for psychopathology based on their direct associations with other features across time. ADHD symptoms and working memory each had direct, independent associations with depression. Results also demonstrated tightly linked co-development of ADHD symptoms and temperamental irritability, consistent with the possibility that this type of anger dysregulation is a core feature that is co-expressed as part of the ADHD phenotype for some children.